The effect of supplying different water level on paddy growth / Nur Sakina Mohd Takerim - Mohd Takerim, Nur Sakina (Faculty of Plantation and Agrotechnology, 2018)
A greenhouse trial was carried out to find out the effect of paddy (Oryza sativa L.) growth performance with different water level supplied. Variety was used for this study is MR219. Maturation period for this variety is 105 to 112 days. To produce the high production of the rice we need to start with water management which mean supply enough and suitable water level for paddy growth. The objectives of this study are to evaluate the effect of water level on the performance of paddy and to study the requirement of water level for the best growth of paddy. Paddy were cultivated with application of four (4) different levels of water. This study was conducted in controlled condition to avoid the impact of rain. From this research, showed that different water level gives the effect on performance of paddy in term of plant height, number of tillers, number of reproductive tillers and grain weight. The result showed that Treatment 4 is 12 cm of water per pot give the best performance. Treatment 4 has the highest plant height, number of reproductive tillers and grain weight.